Internalisasi Nilai Kasih: Membangun Etika Interaksi Sosial Siswa SMA Yadika Soreang - Pasaribu, Ranto Indra (Jurnal Pengabdian Masyarakat, 2026)
Character building in adolescents within the school environment requires an approach that touches upon both spiritual and emotional aspects to address complex social interaction challenges. This community service aims to internalize the values of love to build healthy social interaction ethics for students at SMA Yadika Soreang, Bandung Regency. The selection of this topic is based on the importance of empathy and solidarity in preventing interpersonal conflicts and bullying in schools. The method used was a spiritual gathering employing dialogic lectures, social simulations, and participatory group discussions involving 40 students. The results indicated a 92% increase in students' understanding regarding the concept of harmonious interpersonal relationships. Students were able to demonstrate peaceful conflict resolution methods and showed increased empathy toward peers during simulation sessions. In conclusion, this activity successfully strengthened students' moral foundations in interacting, contributing positively to a more supportive and inclusive school environment.